PELATIHAN, PENGAWASAN DAN PEMBERDAYAAN, PENGARUHNYA TERHADAP KOMITMEN ORGANISASIONAL - Yakup Yakup (Bina Ekonomi, 2018)
ABSTRACTThis study aims to determine the effect of training, supervision and empowerment against organizational commitment of National Education Service Official of Bone Bolango Regency. The data used in this study is the primary data sourced from the filling questionnaire. The population of this research is 62 employees using census method. The analytical technique used to answer the research problem and test the hypothesis is multiple regression analysis with the help of Statistical Product Service Solution (SPSS) software used to analyze the data. The findings of this research there are positive and significant impacts of training, supervision and empowerment toward  Organizational Commitment of National Education Service Official of Bone Bolango Regency.Keywords: training; supervision; empowerment; organizational commitment